Farmer to farmer exchange visit - an effective way of scaling agroecological innovations - M'hamed, Hatem Cheikh; Rudiger, Udo (2024)
The video shows farmers of six different farmer organizations and NARES partners exchanging about technologies like mixed forages, compost, olive, sulla and carob tree production.